2017
DOI: 10.1096/fj.201600882r
|View full text |Cite
|
Sign up to set email alerts
|

A novel tarantula toxin stabilizes the deactivated voltage sensor of bacterial sodium channel

Abstract: Voltage-gated sodium channels (Na V s) are activated by transiting the voltage sensor from the deactivated to the activated state. The crystal structures of several bacterial Na V s have captured the voltage sensor module (VSM) in an activated state, but structure of the deactivated voltage sensor remains elusive. In this study, we sought to identify peptide toxins stabilizing the deactivated VSM of bacterial Na V s. We screened fractions from several venoms and characterized a cystine knot toxin called JZTx-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…The mutation study showed that JZTx-14 acted on NaChBac by binding to the S3–4 extracellular loop, with the 108th phenylalanine (F108) being the key residue. This action mode resembled the previously reported NaChBac channel toxin JZTx-27, although their key residues in the channel were different [ 29 ]. We speculate that JZTx-14 trapped the NaChBac voltage sensor in the deactivated state as it positively shifted the activation kinetics.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The mutation study showed that JZTx-14 acted on NaChBac by binding to the S3–4 extracellular loop, with the 108th phenylalanine (F108) being the key residue. This action mode resembled the previously reported NaChBac channel toxin JZTx-27, although their key residues in the channel were different [ 29 ]. We speculate that JZTx-14 trapped the NaChBac voltage sensor in the deactivated state as it positively shifted the activation kinetics.…”
Section: Discussionsupporting
confidence: 85%
“…It was also active on bacterial Na V s NaChBac and NsvBa, as revealed by our previous screening analysis of spider venom peptides for bacterial Na V s antagonists. However, the toxin was not deeply explored as a bacterial Na V toxin, as it was approximately 10 folds less potent than the toxin JZTx-27, which was investigated in our previous study [ 29 ]. This toxin was purified to homogeneity ( Figure 1 B,C), and its molecular weight was determined as 3422.17 Da (M + H + ) ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the mechanism of AGAP/W38F inhibiting H V 1 channel with that of Zn 2+ , as well as that of some other gating modifier toxins inhibiting Na V and K V channels. Our electrophysiological data suggest that AGAP/W38F inhibition of H V 1 channel shared a canonical voltage‐sensor trapping mechanism with gating modifier toxins inhibiting Na V and K V channels (Lee, Wang, & Swartz, ; Tang et al, ; Xiao et al, ). AGAP/W38F and Zn 2+ act on H V 1 channel with certain similarities.…”
Section: Discussionmentioning
confidence: 84%